Chile : Technical Assistance Report-Forming an Integrated Supervisory Authority. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2020)
This Technical Assistance Report paper on Chile advices on the planned integration of the superintendency for banking supervision, Superintendencia de Bancos y Instituciones Financieras (SBIF), into the Comision para el Mercado Financiero (CMF). While the approved Bills contain important enhancements to the governance and regulatory framework, several legal aspects would benefit from further clarification. These include aspects related to the mandate, objectives, powers, and governance of the CMF. This report discusses the mission's main observations and recommendations regarding the integration of the SBIF into the CMF. The report also provides an overview of the existing supervisory architecture and discusses the legal mandate, objectives, and powers of the new CMF, followed by a discussion on the governance arrangements that existed prior to the integration and of the main changes brought in the Law recently approved. It also discusses a possible blueprint for the organizational structure of the new CMF aimed at realizing the desired synergies in the supervision function and strengthening conglomerate supervision.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet